Nátěry pro cementotřískové desky určené do nepříznivých expozičních podmínek - Vöröšová, Sabina (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Cílem diplomové práce je navrhnout a ověřit nátěrové hmoty pro povrchovou úpravu cementotřískových desek, s cílem zlepšení jejich odolnosti vůči nepříznivým vlivům exteriéru, při zohlednění estetické funkce povrchové úpravy.

The main goal of the dissertation is to design and verify coatings for surface finish of cement bonded particleboards with the aim of improvement of their resistance against the unfavorable influences of the exterior taking into account the aesthetic function of the surface finish.
Coatings for cement bonded particleboards exposed in severe conditions
Keywords: Cementotřísková deska; povrchová úprava; nátěrové hmoty; Cement bonded particleboards; surface finish; coating